Human rights between universality and Islamic legitimacy - Bassiouni, Mahmoud (Studies in comparative political theory, 2024)
"Historically, the dynamics underlying contemporary Muslim human rights discourse and the related question of identity can be traced back to the second half of the nineteenth century. Faced with European superiority and aware of their own need for reform, Muslim intellectuals pondered how to explain the stagnation of Islamic societies and what initiatives were needed to bring about the desired progress. Many Muslims were troubled not only by Europe's material superiority, but also by the sense of inferiority they felt in the face of Europe's ideological defamation of Islamic societies. "Any person," wrote the French philosopher Ernest Renan in 1883, "with a modicum of instruction in the affairs of our time clearly sees the current inferiority of Muslim countries, the decadence of the states governed by Islam, the intellectual nonentity of the races that derive their culture and education solely from this religion." Thus, the idea of reform derived its impetus from an ideological challenge that saw the causes of Muslim stagnation as residing in Islam and identified the latter as inhibiting, or even blocking, the progress of Islamic societies. Accordingly, the crisis of the Muslim search for identity unfolded in response to the question of how to define oneself in relation to Europe and what role Islam should play in this regard. In a broader sense, Muslims were confronted with the basic questions of political philosophy: What principles should we live by, and where do we derive these principles from? Can the principles of a modern society be derived from Islam? Or is it necessary to refer to the ideas and institutions of Europe? To what extent can we then still define ourselves as Muslims in relation to Europe? In response to these questions, three broad currents of thought can be identified. 2.1 Trialogue of Identities Echoing the European position, a secularist school of thought believed that Muslims, by virtue of their religion, were intellectually incapable of developing progressive thought in the European sense. According to this view, Islam was fundamentally incompatible with science and modern civilization. Muslims should therefore accept European modernity as the ultimate frame of reference and assimilate to Europe as much as possible. Politically, this assimilationist stance became most prominent in Turkey. In contrast, a second, much broader current of thought, which might be called traditionalist, argued that the plight of Muslims was due to colonization and oppression by the European West. According to this view, the stagnation of Islamic societies was caused by the exercise of European imperial power, to which Muslims had fallen victim, so that adopting European ideas would be tantamount to intellectual capitulation. Rather, Muslims should seek and rediscover their strength in their own past. The only way to express one's true identity, according to this argument, is to return to one's own tradition"--